2020
DOI: 10.1111/ene.14423
|View full text |Cite
|
Sign up to set email alerts
|

Striatal connectivity in pre‐manifest Huntington’s disease is differentially affected by disease burden

Abstract: Background and purpose: Different amounts of cumulative exposure to the toxic mutant form of the huntingtin protein might underlie the distinctive pattern of striatal connectivity in pre-manifest Huntington's disease (pre-HD). The aim of this study was to investigate disease-burden-dependent corticalstriatal and subcortical-striatal loops at different pre-HD stages. Methods: A total of 16 participants with pre-HD and 25 controls underwent magnetic resonance imaging to investigate striatal structural and functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…No significant differences were found between the close-toonset subgroup and healthy controls. There was also no difference between the total premanifest group and controls with regard to functional connectivity of the right caudate nucleus, bilateral putamen, and bilateral nucleus accumbens [105]. These differences in activity and locations sometimes differ from each other, partly due to differences in task designs.…”
Section: Task-based Fmrimentioning
confidence: 78%
See 1 more Smart Citation
“…No significant differences were found between the close-toonset subgroup and healthy controls. There was also no difference between the total premanifest group and controls with regard to functional connectivity of the right caudate nucleus, bilateral putamen, and bilateral nucleus accumbens [105]. These differences in activity and locations sometimes differ from each other, partly due to differences in task designs.…”
Section: Task-based Fmrimentioning
confidence: 78%
“…Other studies showed that diffusion imaging could be used as a method to differentiate the subgroup close-to-onset premanifest HDEGC from far-from-onset HDEGC. They showed an increased MD in close-toonset-HD, compared to far-from-onset and healthy controls [104,105].…”
Section: Diffusion Tensor Imagingmentioning
confidence: 92%
“…However, due to the severe brain damage, the clinical symptoms of cognitive impairment still appeared. The functional reorganization of CAU_L might underlie compensatory plasticity mechanisms ( Pini et al, 2020 ; Zhang et al, 2021 ). However, CAU_R efficiency decreased in iPSCI.…”
Section: Discussionmentioning
confidence: 99%
“…90 When this study commenced, no cognitive assessments were universally accepted except the UHDRS cognitive score, which also lacks sensitivity, and TFC was discounted consider- 94 Likewise future trials should capitalize on volumetric MRI and connectivity measures. 95,96 Additional trial design measures might include enrichment strategies to recruit patients predicted to have faster rates of progression based on neuroimaging analyses, genetic polymorphisms, clinical profiles, or retest effects 85,[97][98][99][100] to increase the likelihood of demonstrating treatment efficacy with small cohorts over shorter durations.…”
Section: Protocol Designmentioning
confidence: 99%
“…New tracers, such as ligands to phosphodiesterase‐10A, an enzyme expression by striatal MSN whose reduction is one of the earliest biochemical changes in HD 93 may prove to be a reliable indicator of disease progression 94 . Likewise future trials should capitalize on volumetric MRI and connectivity measures 95,96 …”
Section: Future Challengesmentioning
confidence: 99%